Preverjanje matematičnega znanja - Felda, Darjo (Revija za elementarno izobraževanje, 2018)
Assessing Mathematical Knowledge. Mathematical knowledge is assessed at school, in national assessments of knowledge and as part of international research studies. Different knowledge assessments have distinct aims, but they should nevertheless be broadly comparable. In recent decades, Slovenianprimary schools have seen a major increase in the share of students with aboveaverage achievements. However, a comparison of final grades in Grade 9 of primary school with results from the national assessment of knowledge indicates the potentially subjective nature of school grades in mathematics, which would seem to question their purpose. The national assessment of knowledge, whose results correspond with the results of international studies (TIMSS), could be used to adjust knowledge assessment criteria and gradually ensure that knowledge assessment becomes fairer and more objective.DOI: 10.18690/rei.11.2.175-188.2018COBISS-ID: 1540418244
Keywords: mathematical knowledge; national assessment of knowledge; achievements; internal knowledge assessment; final grades